Essentials of project and system engineering management - Eisner, Howard, 1935- (John Wiley & Sons, 2008)
This book is an update to the second edition of Essentials of Project and Systems Engineering Management, published in 2003. The focus on combining project management and systems engineering (two "hot" areas in business today) has made this book unique on the market.